2007
DOI: 10.1002/j.2333-8504.2007.tb02070.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Automated Diagnosis and Instruction for Mathematics Problem‐solving

Abstract: ETS and the ETS logo are registered trademarks ofEducational Testing Service (ETS). AbstractThe past several decades have seen numerous approaches toward automated diagnosis and instructional support of students engaged in mathematics problem-solving. These approaches typically involve detailed analysis of potential solution paths for problems, formal representations of correct and incorrect answers, and support in the form of feedback or explanations to students during the process of solving a problem. The ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(16 reference statements)
0
1
0
Order By: Relevance
“…In a recent report, Underwood (2007) reviewed six such systems for mathematics problem solving and identified them along several dimensions, including: How knowledge, skills, and abilities (KSAs) were represented, how levels of proficiency for the KSAs were determined, and whether common errors were identified. She found that while all six systems were designed to identify common errors, they varied with respect to how the KSAs were represented and how the KSA proficiency levels were determined.…”
mentioning
confidence: 99%
“…In a recent report, Underwood (2007) reviewed six such systems for mathematics problem solving and identified them along several dimensions, including: How knowledge, skills, and abilities (KSAs) were represented, how levels of proficiency for the KSAs were determined, and whether common errors were identified. She found that while all six systems were designed to identify common errors, they varied with respect to how the KSAs were represented and how the KSA proficiency levels were determined.…”
mentioning
confidence: 99%